Respuesta :
Answer:
this copy and paste is to hard to read making it impossible to solve sorry.
Step-by-step explanation:
The value of the expression is 256.
What is simplification of an expression?
Simplification of an expression is the process of writing an expression in the most efficient and compact form without affecting the value of the original expression. It involves, multiply out the brackets and then simplify the resulting expression by collecting the like terms.
For the given situation,
The expression is $x^{6} + (y^{2} \div z^3)\cdot w^3$
⇒ [tex]x^{6}(\frac{y^{2} }{z^{3} } )(w^{3} )[/tex]
Substitute $x=2$, $y=3^2$ = 9$, $z=3$, and $w=4$,
⇒ [tex]2^{6}(\frac{9^{2} }{3^{3} } )(4^{3} )[/tex]
⇒ [tex]64+(\frac{81}{27} )(64)[/tex]
⇒ [tex]64+(3)(64)[/tex]
⇒ [tex]64+192[/tex]
⇒ [tex]256[/tex]
Hence we can conclude that the value of the expression is 256.
Learn more about simplification of an expression here
https://brainly.com/question/13730519
#SPJ3